Escrevivências, as lembranças afrofemininas como um lugar da memória afro-brasileira: Carolina Maria de Jesus, Conceição Evaristo e Geni Guimarães - Amanda Crispim Ferreira (2013)
This work aims to observe the african female escrevivência write-living african- Brazilian collective memory, who was invisibilized in the official records. We believe that memory is the driving spring of black women writing, therefore we set these texts, individual memories of these women, to access historical memory, social and cultural african- Brazilian, in a recent context of abolition and republic from Brazil in the first half of the twentieth century. We will discuss also about writing itself and the concepts of autobiography, and write-living, published by this writer and researcher Conceição Evaristo. To accomplish this analysis, we selected texts in prose and poetry of african-Brazilian writers Carolina Maria de Jesus, Conceição Evaristo and Geni Guimarães, in order to contribute to the (re) building (s) ID (s), retrieve the mutilated story ancestry and black referentiality in Brazil.